Guinea : Poverty Reduction Strategy Paper: Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
Guinea's 2007-10 Poverty Reduction Strategy Paper is intended to reestablish strong, sustainable economic growth in a favorable political and institutional context. The percentage of underweight children under age five has increased from 25.8 percent in 2005 to 26.1 percent in 2008, indicating a slight increase in malnutrition. The coverage of vaccination against measles for children under age one declined from 85.3 percent in 2007 to 65.4 percent in 2008. The number of health centers nationwide remains unsatisfactory despite a modest increase from 399 in 2007 to 410 in 2009.